Green tea - health benefits and applications - Hara, Yukihiko (Marcel Dekker, 2011)
A comprehensive overview of the inherent properties, chemical and biochemical functions, actions for lowering the risks of cardiovascular and infectious diseases and cancers, and underlying mechanisms of tea polyphenols. It reveals the bioantimutagenic potency of epigallocatechin gallate (EGCg) found in green tea.